Spinal anesthesia in laparoscopy for infertility - Nijhawan, Dushyant M.; Shembekar, Manisha C.; Upadhye, Jayshree J. (International Journal of Advances in Medicine, 2018)
Background: Spinal anesthesia in laparoscopy for infertility is coming up as a safe and effective alternative to general anesthesia with endotracheal intubation. This retrospective study was undertaken to evaluate the efficacy of spinal anesthesia in laparoscopy for infertility. Methods: In this retrospective observational study, a total of 100 patients had laparoscopic procedure done during the period January 2017 to December 2017 and were included in the study. Laparoscopic surgeries were performed under general anesthesia. Results: In our study of 60 patients, 30 (50%) patients underwent diagnostic laparoscopy and 30 (50%) patients underwent operative laparoscopy. Additional analgesia was required in 20 (33.33%) of patients. These patients either had longer operative time for more lengthy procedures or were more anxious. 55 (91.66%) patients were discharged from the hospital in less than 12 hours, 1 (1.66%) patient was discharged within 24 hours while 4 (6.66%) patients were discharged after 24 hours in whom lengthy procedures were performed. Post spinal headache was seen in 22 (36.33%) patients, nausea and vomiting in 20 (33.33%) patients, hypotension in 18 (30%) patients. Conversion to general anesthesia was needed in 3 (5%) patients due to longer operative time. Conclusions: Spinal anesthesia in laparoscopy for infertility is a safe and effective alternative to general anesthesia with endotracheal intubation.